The Effectiveness of Gastrectomy With Chemoradiotherapy Among Stage IV Gastric Adenocarcinoma: A Population-Based Analysis - Li, Shuchun; Zang, Lu (Frontiers in Oncology, 2020)
Objectives: The strategy for the treatment of stage IV gastric cancer remains controversial. The objective of this study was to assess whether tumor resection is beneficial to survival in gastric cancer patients with incurable stage IV disease. Methods: This is a retrospective cohort study of gastric cancer patients in the Surveillance, Epidemiology, and End Results (SEER) database between 2010 and 2015. Due to the baseline bias, 1:1 propensity score matching (PSM) was used in this cohort. Patients were grouped by treatment, (1) gastrectomy with chemoradiotherapy (CRT) or (2) CRT only, and a Cox proportional hazards regression model was used to identify predictors of survival. Overall survival was compared between the two groups using the Kaplan-Meier method. Result: After propensity score matching, 162 stage IV gastric cancer patients diagnosed from 2010 to 2015 were identified. Among these patients, half underwent gastrectomy with CRT, while the others received CRT only. The median overall survival rates were 22 months from the date of surgery for the gastrectomy with CRT group and 9.0 months for CRT only group. In the multivariable Cox regression analysis, surgery was associated with a significant improvement in overall survival [hazard ratio (HR) of death =0.31, 95% confidence interval (CI) =0.21-0.46, P<0.0001]. Conclusion: In conclusion, stage IV gastric cancer is still a fatal disease. This population-based study found that compared with CRT alone, CRT with gastrectomy may be associated with a survival benefit in patients with metastatic GC. In selected patients’ survival can be prolonged when the primary tumor is removed. Prospective, randomized trials are required to determine the best strategy for metastatic GC and to describe the characteristics of the selected patients.